Cuando dominan los extremos se hace imposible el consenso democrático: Entrevista a Antonino Espinosa Laña - Cazana, Serapio (Mercurio Peruano, 2020)
At 82 years old, Antonino Espinosa Laña has seen the history of the last fifty years of Peru pass from a privileged space: that of founder, leader and ideologist of the Christian Democratic and Christian Popular parties, whose ideals he himself wrote. And, although both movements never came to power directly, Espinosa worries less about that than about another pending task: the diffusion of Christian social thought in the country. "For the serious politician, winning is convincing."